The Development of English Grammar Book Through Direct Method: Research and Development Study at Mambaus Sholihin English Course - Imam Nur Aziz (Prodi Bahasa Arab dan Lembaga Bahasa Institut Pesantren KH Abdul Chalim Mojokerto, 2020)
Purpose - This research aims to understand the development of English book material for Grammar at Mambaus Sholihin English Course (MEC) Gresik. Design/methodology/approach - This research applied the Educational Research and Development (RnD) to develop the contents. This research method deals with the researcher’s purpose wants to be aimed by need analysis, drafting the document, organizing material, review, expert validation, revision I, try out, and correction II. Findings - This product has been suitable for the students’ needs to help them in learning grammar to be easier understood and practiced. The result shows that book is appropriated with the purposed to help them who need this research and development in relaxed and fun learning of grammar notification. Also, this book is completed with direct method although it is used in speaking skill more, it is also suitable for grammar in learning and teaching. Originality/value - It is important for a teacher or tutor to innovate in designing a teaching book that suits the needs of students. Especially for students who do not have a study handbook. Paper type – Research paper